2021
DOI: 10.1016/j.heliyon.2021.e07265
|View full text |Cite
|
Sign up to set email alerts
|

Saussurea lappa plant rhizome extract-based zinc oxide nanoparticles: synthesis, characterization and its antibacterial, antifungal activities and cytotoxic studies against Chinese Hamster Ovary (CHO) cell lines

Abstract: The plant extracts are known for their anti-inflammatory, antifungal, antiviral and antibacterial properties. The use of plant extracts in the preparation of bio-materials increases their biological application. In this concern, herein reporting an eco-friendly procedure which is also a simple and cost effective, for the synthesis of Zinc Oxide nanoparticles (ZnONPs) using Saussurea lappa plant root (rhizome) extract as a fuel. The prepared nanoparticles were confirmed using various characterization techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 79 publications
2
9
0
1
Order By: Relevance
“…Nanoparticles exhibit a wide range of magnetic and optoelectronic properties that are influenced by their size and form distribution, as well as their composition. Due to the fact that this technique of synthesis eliminates the need for harmful chemicals, as well as its ease and environmental friendliness, the synthesis of nanoparticles employing vegetable extract is becoming increasingly popular [3][4][5]. In addition to its unique characteristics and high excitonic binding energy, zinc oxide (ZnO) is used in this application [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles exhibit a wide range of magnetic and optoelectronic properties that are influenced by their size and form distribution, as well as their composition. Due to the fact that this technique of synthesis eliminates the need for harmful chemicals, as well as its ease and environmental friendliness, the synthesis of nanoparticles employing vegetable extract is becoming increasingly popular [3][4][5]. In addition to its unique characteristics and high excitonic binding energy, zinc oxide (ZnO) is used in this application [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It is routinely possible to synthesize ZnO NPs using various methods, including but not limited to hydrothermal, solvothermal, sol-gel, direct oxidation, chemical vapour deposition (CVD), electrodeposition (ED), sonochemical, chemical bath deposition (CBD), microwave, and other approaches [5]. These approaches, on the other hand, are expensive, hazardous, and unfriendly to the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…To a 100 ml of distilled water added 1 gm of seed powder, then boiled at 70 °C for about 30 min, cooled, filtered, and store at 4 °C in the refrigerator for further use. The root extract of the Saussurea-lappa plant was prepared following the procedure described by the same group [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…From the literature survey, it is observed that the Ocimum species used for the synthesis of silver [ 42 , 43 ], gold [ 44 ], platinum [ 45 ], copper [ 46 ] and zinc [ 47 ] oxide nanomaterials. Saussurea lappa plant rhizome extract was utilized in the synthesis of silver [ 48 ], magnesium [ 49 ] selenium [ 50 ], and zinc oxide [ 51 ] nanoparticles but no literature on the synthesis of copper oxide (CuO) nanoparticles. In addition, best of our knowledge, there is no literature available on the synthesis of copper oxide (CuO) nanoparticles using a mixture of both Ocimum sanctum and Saussurea lappa plant extracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation